2010
DOI: 10.1007/s10397-010-0648-2
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of quality of reporting in randomised controlled trials to prevent hypotension after spinal anaesthesia for caesarean section

Abstract: Hypotension is a frequent complication of spinal anaesthesia for caesarean section and can threaten the well-being of the unborn child. Numerous randomised controlled trials (RCTs) dealt with measures to prevent hypotension. The aim of this study was to determine the reporting quality of RCTs using the Consolidated Standards of Reporting Trials (CONSORT) statement since low quality can lend false credibility to a study and overestimate the effect of an intervention. We performed a systematic literature search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…None of the studies stated who generated the allocation sequence and whether the same person enrolled the participants. In our opinion (and that of others), a marked improvement in the items relating to randomization was found [55]. Just over half the studies (n = 15) fully described the methods used to generate the allocation sequence.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…None of the studies stated who generated the allocation sequence and whether the same person enrolled the participants. In our opinion (and that of others), a marked improvement in the items relating to randomization was found [55]. Just over half the studies (n = 15) fully described the methods used to generate the allocation sequence.…”
Section: Discussionmentioning
confidence: 52%
“…Reporting of a priori sample size calculation is an indicator of adequate trial planning and indicates whether a trial ends earlier than planned. However, Herdan A. et al [55] reported that sample size calculation showed a sharp increase over time, i.e. the percentage of trials correctly reporting this item increased from 23% (three of 13 reports) to 71% (17 of 27 reports) in the post-CONSORT period.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, an unpredictable and unknown allocation schedule can minimize selection and confounding biases. 41 However, we found none of the trials reported detailed information on the implementation of randomization. None of the studies stated who generated the allocation sequence and who enrolled the participants.…”
Section: Discussionmentioning
confidence: 86%
“…Randomization reduces confounding by equalizing so‐called factors (independent variables) that have not been accounted for in the RCT. In addition, an unpredictable and unknown allocation schedule can minimize selection and confounding biases 41 . However, we found none of the trials reported detailed information on the implementation of randomization.…”
Section: Discussionmentioning
confidence: 93%
“…Since the severity and persistence of hypotension will lead to acidosis in the fetus, appropriate measures should be taken to prevent the onset or the continuation of hypotension in the mother during the process of anesthesia and C-section. Several pharmaceutical and non-pharmaceutical strategies have been introduced for preventing the spinal anesthesia-induced hypotension [18,19]. Administration of colloidal fluid before surgery, injection of crystalloid fluid during surgery and administration of vasopressors are among the pharmaceutical methods, while use of bandages in lower extremities and alternating compression devices are among the non-pharmaceutical methods [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%